The effect of Plantago major supplementation on leptin and VEGF-A serum levels, endothelial dysfunction and angiogenesis in obese women – a randomised trial. Issue 4 (27th January 2021) - Skrypnik, Damian; Skrypnik, Katarzyna; Pelczyńska, Marta; Sobieska, Magdalena; Tinkov, Alexey A.; Suliburska, Joanna; Bogdański, Paweł
Abstract : Plantago major oral supplementation increases serum leptin level and enhances leptin influence on VEGF serum level increase in obese women. Abstract : Obesity is associated with increased serum leptin level, endothelial dysfunction and angiogenesis. In vitro studies have shown that vascular endothelial growth factor (VEGF) synthesis is increased by leptin. Animal studies revealed the effectiveness of Plantago supplementation treatment of obesity. The study aim was to evaluate the effect of Plantago major supplementation on serum leptin and VEGF blood concentration, endothelial dysfunction and angiogenesis in obese women. Seventy-two obese women received oral Plantago major supplement ( Plantago group, n = 35) or placebo (placebo group, n = 37) for 12 weeks. At baseline and after completion, anthropometric and body composition measurements were performed, and blood samples were collected. Serum concentrations of leptin, VEGF-A, adiponectin, tumour necrosis factor α and soluble intercellular adhesion molecule have been determined. At completion, the leptin level was higher in the Plantago group (39 781.55 ± 20 360.73 pg ml −1 ) compared to both the baseline (36 138.71 ± 25 401.51 pg ml −1 ) and placebo group (30 502.81 ± 19 003.18 pg ml −1 ). Also, leptin concentration in the Plantago group at completion correlated positively with an increase in VEGF-A level ( R = 0.45), and baseline VEGF-A level correlated negatively with the increase in leptin concentration ( R = −0.47). Plantago major supplementation increases leptin serum level, enhances leptin influence on VEGF-A serum level increase and by this mechanism may intensify endothelial dysfunction and angiogenesis in obese women.